2017
DOI: 10.1161/circgenetics.117.001809
|View full text |Cite
|
Sign up to set email alerts
|

Identity-by-Descent Mapping Identifies Major Locus for Serum Triglycerides in Amerindians Largely Explained by an APOC3 Founder Mutation

Abstract: Background Identity-by-descent (IBD) mapping using empirical estimates of IBD allele sharing may be useful for studies of complex traits in founder populations, where hidden relationships may augment the inherent genetic information that can be used for localization. Methods and Results Through IBD mapping, using ~400,000 SNPs, of serum lipid profiles we identified a major linkage signal for triglycerides (TG) in 1,007 Pima Indians (LOD=9.23, p=3.5×10−11 on chromosome 11q). In subsequent fine-mapping and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…The loss-of-function mutations rs147210663, rs76353203, and rs138326449 in APOC3 have been robustly linked to favorable lipid profiles and reduced risks of CVD ( 46 , 47 ). rs147210663 has been reported to have particularly strong effects on serum triglyceride levels in Pima Indians, lowering triglyceride levels by 42% ( 48 ). In our data set, the frequency of this variant was highest in Ashkenazi Jews (MAF = 1.1%) and rare in all other populations, including Latinos (MAF < 0.1%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss-of-function mutations rs147210663, rs76353203, and rs138326449 in APOC3 have been robustly linked to favorable lipid profiles and reduced risks of CVD ( 46 , 47 ). rs147210663 has been reported to have particularly strong effects on serum triglyceride levels in Pima Indians, lowering triglyceride levels by 42% ( 48 ). In our data set, the frequency of this variant was highest in Ashkenazi Jews (MAF = 1.1%) and rare in all other populations, including Latinos (MAF < 0.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, genetic profiles of populations not represented in this data set might yield exciting additional information about apolipoprotein diversity. Examples for such insights based on population isolates or founder populations are effects of the triglyceride-lowering APOC3 variants rs147210663 in Pima Indians (MAF = 2.6%) ( 48 ) and rs138326449 in Hutterites (MAF = 2.2%) ( 67 ), as well as the LDL risk variant rs5742904 in APOB in Old Order Amish (MAF = 12%) ( 68 ). With decreasing sequencing costs, we anticipate that the sequencing of founder populations will continue to represent a powerful tool for genetic research of apolipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…The association of genotypes with maximum BMI observed in the longitudinal study was analyzed in 6,789 participants by a linear mixed model fitted with a variance‐components covariance structure to account for genetic relatedness among individuals. The genetic‐relatedness matrix was estimated as the proportion of the genome shared identically by descent (IBD) between each pair of individuals who had been genotyped (a total of 29,648,850 pairs) . Genomic segments shared IBD were identified with the fastIBD function of the Beagle (version 3.3.2, the University of Washington, Seattle, WA) package using 482,616 autosomal markers with a minor allele frequency > 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…This population has very high prevalence of obesity and type 2 diabetes and has been deeply characterized for metabolic traits [12][13][14] . Previously, genetic studies have been conducted in this population with specific focus on metabolic traits, including genome-wide linkage analyses 15 , genome-wide association studies (GWAS) [16][17][18][19][20] , assessment of genes and/or variants found in GWAS studies in other ancestry groups [21][22][23][24][25][26] , and targeted sequencing of physiologic candidate genes [27][28][29][30][31][32] . These approaches have found common and rare variants that are associated with metabolic traits and disease status in this population; however, a systematic examination of coding variation across the genome and its potential impact has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%